A proposed English proficiency test in grammar for six Asian student groups - Manilay, Francisca Alcantara 1930- (s.n.], 1971)
This is an 80-minute partial production test in English grammar, the second part of a 3-part English proficiency test for Asian students. It has been constructed along the new dimensions in language testing and designed to measure Asian students' control of the grammatical structures of English. It aims to serve Philippine colleges and universities that recognize the value of English tests as evaluative and predictive measures of Asian students' academic success.